2009
DOI: 10.1108/17465729200900024
|View full text |Cite
|
Sign up to set email alerts
|

‘No one knows like we do’ — the narratives of mental health service users trained as researchers

Abstract: In 2008, Mind in Bexley received a research development grant from the Big Lottery Fund and a training grant from Bexley Care Trust to empower service users to participate and contribute to a pilot research project. The project aims were to work with, develop, train and support service users as researchers, in order to record the narratives of service users who have common experiences of mental health distress and treatment. The research development project set up an advisory group, created and developed a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(47 citation statements)
references
References 11 publications
(12 reference statements)
0
46
0
1
Order By: Relevance
“…, ; Palmer et al . ). Some studies reported that collaborative research required training and both individual support and group support had a valuable role (Callander et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…, ; Palmer et al . ). Some studies reported that collaborative research required training and both individual support and group support had a valuable role (Callander et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Hutchinson & Lovell ; Palmer et al . ). User‐researchers considered it important that training contained both formal and informal networking (Moltu et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…En effet, les services communautaires jouent un rôle de soutien essentiel dans le rétablissement des personnes atteintes d'un trouble mental (59). Le médecin compétent dans son rôle de promoteur de santé doit donc être capable de « repérer les groupes marginalisés au sein des populations servies et y répondre de la façon appropriée » (60), notamment en pouvant les orienter vers des ressources dans la communauté qu'il peut ainsi mieux connaître grâce à l'éclairage particulier et unique du patient partenaire (61). Avec le temps, l'implication des personnes utilisatrices de services à titre de partenaire de recherche, de soin ou d'enseignement conditionne des relations plus égalitaires (62) et moins paternalistes (63) entre les professionnels et les usagers.…”
Section: Resultsunclassified
“…Indeed the use of the university as a base for the work as found by others (Palmer et al, 2009) can be seen to have added to the co-researchers' confidence and sense of self worth as it became apparent that attending meetings at the university was itself experienced as a valuable part of the overall experience with an observable increase in skills and confidence.…”
Section: Place and Spacementioning
confidence: 97%